Influence of mildly and moderately elevated pulmonary artery systolic pressure on post‐renal transplantation survival and graft function. Issue 1 (9th November 2018) - Wang, Stephani C.; Garcia, Rachel; Torosoff, Mikhail; Fein, Steven A.; Ashar, Ata; Chandolias, Nikolaos; Conti, David; Lyubarova, Radmila
Abstract : Background: Severe pulmonary hypertension (PH) has been associated with decreased post–kidney transplant survival and increased rate of long‐term cardiovascular complications. Despite a high prevalence of PH in patients with end‐stage renal disease, data on post‐transplant renal allograft survival in recipients with pre‐existing mild‐to‐moderate PH are limited. Methods: The single‐center retrospective study cohort consisted of 192 consecutive (2008–2015) renal transplant recipients with documented pretransplantation transthoracic echocardiogram (TTE) pulmonary artery systolic pressure (PASP). Mean age was 50.9 ± 12.4 years, 36.5% were females, and 81.25% were Caucasians. Results: Elevated PASP ≥ 37 mm Hg was present in 51 patients. Elevated PASP was more common in patients with decreased <50% left ventricular ejection fraction (13.73% vs 3.55%, P = 0.010); otherwise, there were no significant differences in baseline demographic (age, ethnicity, gender, and donor status) and clinical parameters between patients with normal and elevated PASP. Four‐year mortality (5.7%) was not significantly affected by elevated PASP. However, elevated PASP was associated with significantly decreased estimated glomerular filtration rate (eGFR) at 1 year (52.26 vs 60.13 mL/min, P = 0.019) and 2 years (51.04 vs 60.28 mL/min, P = 0.006) post‐transplant. Conclusion: Mild and moderately elevated pre–kidney transplant PASP does not affect 4‐year post‐transplant mortality or graft loss. However, elevated pretransplant PASP is significantly associated with decreased 1 year and 2 years post‐transplant eGFR. Preoperative echocardiographic evaluation for PH may be useful in predicting the probability of short‐term renal graft and long‐term graft dysfunction in these patients.